Sounder - Armstrong, William H; Barkley, James (New York Harper Trophy, 1969)
angry and humiliated when his sharecropper father is jailed for stealing food for his family, a young black boy grows in courage and understanding by learning to read and through his relationship with his devoted dog sounder
American Corner
Winner The John Newbery Medal Book
11 14
Keywords: English Fiction; English Stories